Exploring the experiences of having a child who regularly does not attend school on parental mental health and wellbeing in the United Kingdom - Jasmine Chavda; Lauren Denyer; Daksha Trivedi; Amanda K. Ludlow (PLoS ONE, 2025)
A significant number of children in the United Kingdom (UK) are counted as regular school non-attendees, with those who are neurodiverse and/or have underlying mental health conditions considered most at risk. Relatively little attention has explored the experiences of having a child who regularly does not attend school on the parents’ own mental health and wellbeing. Thematic analysis was conducted using semi-structured interviews with 11 parents with children who do not regularly attend school in the UK. Two superordinate themes were generated: (1) Pivotal changes to the family dynamic, and (2) Paying a high price. Overall, parents revealed how having a child who did not regularly attend school had negatively impacted their health, wellbeing and their daily life. Many parents acknowledged these experiences had left them needing to access support for their own mental health. These results hold real-world implications for schools, services and health professionals who could provide more personalised support to reduce the negative consequences of school non-attendance. This should be prioritised for children’s overall development and parents’ wellbeing.